2022
DOI: 10.1109/tuffc.2022.3162419
|View full text |Cite
|
Sign up to set email alerts
|

Design, Implementation, and Medical Applications of 2-D Ultrasound Sparse Arrays

Abstract: An ultrasound sparse array consists of a 1 sparse distribution of elements over a 2-D aperture. Such 2 an array is typically characterized by a limited number 3 of elements, which in most cases is compatible with the 4 channel number of the available scanners. Sparse arrays 5 represent an attractive alternative to full 2-D arrays that 6 may require the control of thousands of elements through 7 expensive application-specific integrated circuits (ASICs). 8 However, their massive use is hindered by two main draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 134 publications
0
11
0
Order By: Relevance
“…Consequently, it did not increase between dual array monostatic imaging and bistatic imaging due to the added thermal noise, despite the additional high contrast wall regions between the transducers. Options to reduce the amount of thermal noise could be in hardware improvements such as more sensitive transducers and amplifiers [14]. As stated, the bistatic image formation improves image contrast and resolution, but also introduces some artefacts.…”
Section: Image Quality Assessment In Aorta Phantommentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it did not increase between dual array monostatic imaging and bistatic imaging due to the added thermal noise, despite the additional high contrast wall regions between the transducers. Options to reduce the amount of thermal noise could be in hardware improvements such as more sensitive transducers and amplifiers [14]. As stated, the bistatic image formation improves image contrast and resolution, but also introduces some artefacts.…”
Section: Image Quality Assessment In Aorta Phantommentioning
confidence: 99%
“…Bernal et al changed the transmit aperture between steering angles and found that the image quality can be improved with multiple complementary receiving sparse apertures, thereby decreasing 800 Hz volume rates with a factor 2-4 [13]. Sparse arrays with a higher center element density have also been increasingly used to optimize the homogeneity of the transmit field and non-periodic sampling of the elements to reduce the occurrence of grating lobes [14]. In terms of beam steering, comparisons in acquisition schemes suggest that a higher heterogeneity of compounded multi-angle transmits are favorable to improve both contrast and resolution [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…A straight forward translation to 3-D would give arrays with 192 × 192 = 36,864 elements or 256 × 256 = 65,536 elements yielding data rates of 2,560 GBytes/s, which is clearly not possible to process in real time. This has been solved by making sparse matrix probes, where only part of the elements are connected resulting in higher side lobe levels [1][2][3][4][5][6]. A second approach is to make micro-beamforming in the handle to reduce the amount of data.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a doubling of resolution necessitates quadrupling the total number of elements. Many approaches for making sparse arrays have been suggested [3][4][5][6][7], but they suffer from reduced contrast and reduced penetration depth due to the reduction in active transducer surface area.…”
Section: Introductionmentioning
confidence: 99%